2020
DOI: 10.1186/s13019-020-01262-4
|View full text |Cite
|
Sign up to set email alerts
|

Network construction of aberrantly expressed miRNAs and their target mRNAs in ventricular myocardium with ischemia–reperfusion arrhythmias

Abstract: Background Hypothermic ischemia-reperfusion arrhythmia remains the main factor affecting cardiac resuscitation under cardiopulmonary bypass. Existing research shows that certain miRNAs exhibit significantly different expressions and effects in arrhythmias, however, the effect of miRNAs on the progression of hypothermic ischemic–reperfusion arrhythmias (RA) and its potential mechanism remain to be further explored. Methods Sprague-Dawley (SD) rats were randomly divided i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Amiodarone is a class III antiarrhythmic drug that can delay ischemic myocardial conduction and reduce the action potential of ischemic and nonischemic myocardium, thereby reducing reentrant excitation and triggered activity and helping to inhibit the occurrence of arrhythmia [ 12 ]. Clinical studies have shown that in acute myocardial ischemia or myocardial infarction, amiodarone can increase the activity of ion channels without aggravating the deterioration of cardiac function and has no effect on myocardial ischemia [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Amiodarone is a class III antiarrhythmic drug that can delay ischemic myocardial conduction and reduce the action potential of ischemic and nonischemic myocardium, thereby reducing reentrant excitation and triggered activity and helping to inhibit the occurrence of arrhythmia [ 12 ]. Clinical studies have shown that in acute myocardial ischemia or myocardial infarction, amiodarone can increase the activity of ion channels without aggravating the deterioration of cardiac function and has no effect on myocardial ischemia [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…As an inconsistent Co-DE miRNA, the expression of miR-122-5p varied in intestinal ischemia-reperfusion injury and ischemia-reperfusion induced arrhythmias. 26 MiR-27a-5p had been associated with a decreased level of Bach1 mRNA, which reduced apoptosis in liver ischemia-reperfusion injury. 27 Elsewhere, miR-1247-3p alleviated the damage of myocardial ischemia-reperfusion by targeting both BCL2L11 and caspase-2.…”
Section: Discussionmentioning
confidence: 95%
“…reported that eight dysregulated miRNAs are most closely associated with hypothermic ischaemia–reperfusion arrhythmia in rats, and the miRNA–mRNA interaction network suggested that novel miR-17 may target CJA1 to participate in reperfusion arrhythmias. 86 …”
Section: Mirnas and Arrhythmiasmentioning
confidence: 99%